PENGARUH KREATIVITAS MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA KELAS V SD SWASTA CERDAS BANGSA TAHUN AJARAN 2017/2018 - Eduard Eduard (JURNAL CURERE, 2018)
Type of this research is descriptive research with quantitative methods, namelyresearch on data collected and expressed in the form of numbers by using the correlationformula product moment. The population of the entire grade V SD Swasta CerdasBangsa totalling 25 students. the sample of this research is the whole grade V SDSwasta Cerdas Bangsa totalling 25 students. data collection of creativity teachingteachers taken through spreading the question form to students while the studentlearning outcomes requested from homeroom V SD Swasta Cerdas Bangsa.Results of the study concluded that the average score obtained teachers teachingcreativity (74.36). The average value of the results of learning students obtained grade v(74,04) are on the qualifications of being. The results obtained from the product momentcorrelation with creativity teaching teachers as a bound variable (X) and student learningoutcomes as bound variables (Y) of 0.969898 or 96,9% with significant smaller level0.05. The result of calculations or test hypotheses 19,10 while 2,07 it is greater thanwhile rejected accepted. This means that there are significant effects of creativityteaching teacher against student learning outcomes.